THE EFFECT OF LIFE-STORY-RETELLING TECHNIQUE ON STUDENTS’ SPEAKING FLUENCY - Olivia Heluri Yolanda Putri; Widya Caterine Perdhani; Moh. Hasbullah Isnaini (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2021)
Second or foreign language learners often get difficulty in speaking fluency, which can be called as disfluency. Disfluency can be caused by some problems such as difficult task and lack of practice. Retelling a life story is one of the activities in teaching speaking which can be used by teachers in the EFL classroom. This study aims to find out the effectiveness of using Students’ Life Story by retelling technique in improving speaking fluency. The research design used in this study was Pre-Experimental Research with a quantitative approach. This study was conducted in three meetings. As the instruments, the researchers used the test which was pre-test and post-test. The population of this research is all the students in the 1st grade of Senior High School 3 Lumajang and the researchers took one class of the 1st grade of Senior High School Lumajang to collect the data by using probability sampling. The subjects of this study were 36 students of X Science 6 class at Senior High School 3 Lumajang. This research used pre-experimental research design with quantitative approach by using pre-test and post-test and also the scoring guidance for the assessment to collect the data. The result of this research showed that life-story-retelling technique can help the students in improving their speaking fluency. This study was considered successful when there was a significant result between students’ score in pre-test and post-test. Thus, it can be concluded that life-story-retelling technique successfully improved the students’ speaking fluency.